2004
DOI: 10.1081/ja-200034691
|View full text |Cite
|
Sign up to set email alerts
|

Developing Employment Services for Criminal Justice Clients Enrolled in Drug User Treatment Programs

Abstract: Approximately 80% of parolees have a history of substance abuse and nearly all are unemployed following release from prison. Common stipulations of parole require offenders to obtain employment and to not use mood-altering substances. This article explores a series of strategies implemented from 1999 to 2001 to help offenders paroled to substance user treatment to gain employment. A total of 245 paroled offenders enrolled in an outpatient substance abuse treatment program voluntarily agreed to participate in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…restitution and mediation between offenders and victims) had a moderate impact on reducing youth recidivism (between 10 and 13%) [49]. Additionally, a study conducted in 2004 among adult offenders with a history of drug use found that post-release employment programmes had a high programme completion rate (78%), and more than half secured competitive employment, often including benefits [50]. …”
Section: Discussionmentioning
confidence: 99%
“…restitution and mediation between offenders and victims) had a moderate impact on reducing youth recidivism (between 10 and 13%) [49]. Additionally, a study conducted in 2004 among adult offenders with a history of drug use found that post-release employment programmes had a high programme completion rate (78%), and more than half secured competitive employment, often including benefits [50]. …”
Section: Discussionmentioning
confidence: 99%
“…The short-term positive effects of treatment on subsequent labor force participation have been fairly well documented (Butzin, Scarpitti, Neilsen, Martin, & Inciardi, 1999;French et al, 1993;Hall et al, 2004;Kemp, Savitz, Thompson, & Zanis, 2004;Leukefeld, Webster, Staton-Tindall, & Duvall, 2007). Nevertheless, while some evidence points to the enduring nature of the improved work status resulting from criminal justice-sponsored treatment, with benefits lasting between 3 and 5 years (Butzin et al, 2005;O'Connell, Enev, Martin, & Inciardi, 2007;Sung, 2001), the lack of experimental control or the failure to control for baseline employment differences, or both, in these longitudinal studies renders their findings inconclusive and the contamination from self-selection highly plausible.…”
Section: Introductionmentioning
confidence: 97%
“…Employment and employment-related intervention are said to play important roles in substance user recovery (Kemp et al, 2004;Platt, 1997;Walker & Leukefeld, 2002). However, jump-starting the virtuous cycle of abstinence and employment among criminal offenders poses a daunting challenge to criminal justice authorities and clinical professionals, because of the extreme state of psychosocial deterioration in which most substance-abusing offenders are found (Comeford, 1999;Leukefeld, Mc-Donald, Staton, 2003;Sung, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Evaluations of the few intensive programs that provide job skills training and supported employment show that many participants fail even to maintain their supported employment jobs and many who obtain competitive employment fail to maintain those jobs overtime (e.g., Dickinson and Maynard, 1981;Kemp et al 2004). One of the most extensive and informative studies of employment interventions for illicit drugs users evaluated the effects of an intensive supported work intervention in 1,433 adults who were unemployed and who had been in substance use treatment within 6 months of enrollment in the study (Dickinson and Maynard, 1981).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…However, little research has been conducted to examine the extent to which program participants maintain employment over extended periods of time. The information that is available on longer-term outcomes suggests that many intervention graduates who obtain employment do not reliably maintain their employment over time (e.g., Platt et al 1993;Kemp et al 2004; Dickinson and Maynard, 1981 …”
mentioning
confidence: 99%